Echoes, echoes, echoes, echoes, echoes Cassina, 50 years of iMaestri - Mietton, Ivan; Coccia, Emanuele 1976-; Colomina, Beatriz 1952-; Wigley, Mark 1956-; Dardi, Domitilla 1970-; Lehmann, Barbara; Saraïva, Céline; Withers, Jane (Rizzoli, 2023)
On the Collezione Cassina iMaestri, collection created by Cassina, Italian manufacturing company specialised in the creation of high-end designer furniture, in collaboration with international designers
Abweichender Titelzusatz nur auf Buchbanderole
Keywords: Balla, Giacomo -- 1871-1958; Mackintosh, Charles Rennie -- 1868-1928; Albini, Franco -- 1905-1977; Le Corbusier -- 1887-1965; Eames, Charles -- 1907-1978; Scarpa, Carlo -- 1906-1978; Parisi, Ico -- 1916-1996; Zanuso, Marco -- 1916-2001; Perriand, Charlotte -- 1903-1999; Jeanneret, Pierre -- 1896-1967; Ponti, Gio -- 1891-1979; Asplund, Erik Gunnar -- 1885-1940; Cassina, Cesare -- 1909-; Magistretti, Vico -- 1920-2006; Eames, Ray -- 1912-1988; Rietveld, Gerrit Thomas -- 1888-1964; Geschichte 1900-2023; Sammlung; Wohnkultur; Design; Möbel; Industriedesign